PCDHB17P/miR-145-3p/MELK/NF-κB Feedback Loop Promotes Metastasis and Angiogenesis of Breast Cancer - Zhu, Li; Zhang, Yan-Jun; Wang, Bin; Yang, Li; Zheng, Yi-Qiong; Sun, Lin-De; Tian, Lin; Chen, Tao; Wang, Jian-Dong (Frontiers in Oncology, 2021)
Breast cancer is one of the most common life-threatening cancers, mainly due to its aggressiveness and metastasis. Accumulating evidence indicates that long non-coding RNAs (lncRNAs) participate in the development and progression of breast cancer. Nevertheless, the function and expression level of lncRNAs in breast cancer are still not fully understood. Here, we demonstrated that lncRNA PCDHB17P was up-expressed in human breast cancer tissues and cell lines. Knockdown of PCDHB17P remarkably suppressed migration and invasion as well as tube formation ability of breast cancer cells. MiR-145-3p was significantly decreased in breast cancer samples, which was negatively correlated to the expression of PCDHB17P. In addition, we identified MELK was a direct target gene of miR-145-3p, which was higher expressed in breast cancer tissues than that in adjacent normal tissues. Mechanistic investigation indicated that PCDHB17P acted as a cancer-promoting competing endogenous RNA (ceRNA) by binding miR-145-3p and upregulating MELK. Interestingly, MELK could in turn increase the promoter activity and expression of PCDHB17P via NF-κB, thus forming a positive feedback loop that drives the metastasis and angiogenesis of breast cancer. Overall, the results demonstrated that the constitutive activation of PCDHB17P/miR-145-3p/MELK /NF-κB feedback loop promotes the metastasis and angiogenesis of breast cancer, suggested that this lncRNA might be a promising prognostic biomarker and therapeutic target for breast cancer.